1990
DOI: 10.1121/1.399407
|View full text |Cite
|
Sign up to set email alerts
|

Transmission loss of a multilayer panel with internal tuned Helmholtz resonators

Abstract: Two different methods of analysis are presented for the transmission loss prediction of a multilayer panel with internal Helmholtz resonators. One of the methods, devised at the Lockheed Aeronautical Systems Company, is based on the pressure ratio methodology of Beranek and Work [J. Acoust. Soc. Am. 21, 419–428 (1949)], where the acoustic resonators are included as a side branch. The other method uses a transfer matrix approach where the resonators are embedded in and move with the trim panel. Comparisons are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…1,2 Differently tuned resonators also have been employed to decrease broadband noise. 3 One of the popular shapes of resonator array is a plane-type array illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Differently tuned resonators also have been employed to decrease broadband noise. 3 One of the popular shapes of resonator array is a plane-type array illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The Helmholtz resonator is very efficient in controlling the noise over a narrow frequency band and has been applied successfully in many acoustic enclosures [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors of Ref. 3, their idea stems from the works of Mason and Fahy, 4 Prydz et al, 5 and Kuntz et al, 6 where the HRs where attached directly on the panel. Sugie et al 3 suggested that including the resonant element within the fibrous sound package in between the two panels allows for a more flexible optimization of the HR effect and a low frequency sound insulation improvement.…”
Section: Haisam Osmanmentioning
confidence: 99%